1984
DOI: 10.1073/pnas.81.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of extrachromosomal probes for mutagenesis by carcinogens: site-specific incorporation of O6-methylguanine into viral and plasmid genomes.

Abstract: Organic synthesis and recombinant DNA technology were used to situate a putatively premutagenic DNA lesion, O6-methylguanine (O6MeGua), at a specific location in the genomes of two bacterial viruses, M13mp8 and phi X174, and of the bacterial plasmid pBR322. In each genome the first guanine residue in the unique recognition sequence for restriction endonuclease Pst I (5'-C-T-G-C-A-G-3') was replaced with O6MeGua. This was accomplished by ligating a chemically synthesized tetranucleotide, 5'-pTpm6GpCpA-3', into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 17 publications
1
57
2
Order By: Relevance
“…The cytotoxic effects of DNA-methylating agents have been exploited in their use as potent anticancer agents. O 6 -methyl-guanine (O6MeG) is mutagenic because polymerases frequently misinsert T opposite O6MeG instead of C, both in vivo (9,10) and in vitro (11)(12)(13). In this study, we present the crystal structures of complexes of a high-fidelity DNA polymerase with substrates representing several steps of nucleotide insertion opposite O6MeG.…”
mentioning
confidence: 99%
“…The cytotoxic effects of DNA-methylating agents have been exploited in their use as potent anticancer agents. O 6 -methyl-guanine (O6MeG) is mutagenic because polymerases frequently misinsert T opposite O6MeG instead of C, both in vivo (9,10) and in vitro (11)(12)(13). In this study, we present the crystal structures of complexes of a high-fidelity DNA polymerase with substrates representing several steps of nucleotide insertion opposite O6MeG.…”
mentioning
confidence: 99%
“…This high yield indicated that the tetramer, when present in large excess, was sufficiently complementary to the ligation target for DNA ligase to very effectively form phosphodiester bonds. Electrophoresis followed by autoradiography of the ligation mixture revealed that incorporation of [32p] occurred principally in the circular heteroduplexes (22). The heteroduplex DNA structures that received the modified oligonucleotide had gaps that formed with equal probability in either of the two complementary strands (Fig.…”
Section: Site-specific Incorporation Of 06_ Methylguanine Into a Viramentioning
confidence: 99%
“…The first step in this procedure (22) was to treat the replicative form (RF) of M13mp8 with Pst I (Fig. 2).…”
Section: Site-specific Incorporation Of 06_ Methylguanine Into a Viramentioning
confidence: 99%
See 1 more Smart Citation
“…These nucleophiles are, however, limited to thiols, and do not include more relevant nucleophiles such as enols or phosphate esters (such as GMP). Although negative results with GMP may reflect on the possibility of covalent DNA modification, it must be remembered that mononucleotides significantly underestimate the reactivity of oligonucleotides as nucleophiles (19,20).…”
Section: I< 2cmentioning
confidence: 99%